REGULASI PENDAFTARAN MEREK INTERNASIONAL DALAM UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Cokorda Istri Dian Laksmi Dewi (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2018)
The globalization of crime incised a social reality where crimes can be committed across national borders and have an impact not only on the people of a country, but on the international community. Theoretically, there are several terms that are known to describe acts which are called crimes under international law, namely international crimes, transnational crimes, and national crimes with international dimensions. International crimes are crimes that threaten both directly and indirectly to international peace and security, affect many countries and have universal jurisdiction. The qualification of international crimes refers to crimes regulated in the Rome Statute of the International Criminal Court (Rome Statute circulated as document A / CONF.183 / 9 of 17 July 1998), namely crimes of genocide; crimes against humanity; war crimes; and crime of aggression. Transnational crimes are transnational crimes regulated in international conventions.